2006
DOI: 10.1055/s-2005-872566
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotikaprophylaxe bei Sectio Caesarea - Piperacillin 4 g versus Piperacillin/Tazobactam 4,5 g

Abstract: We did not observe any severe adverse effects. Rate of severe wound infections was 1.3 % (Tazobactam/Piperacillin) and 2 % (Piperacillin alone). The difference showed no statistic significance (p > 0.01). During postoperative course we found a higher increase of CRP (p < 0.01) in the Piperacillin group. CRP proved to be a useful objective parameter to distinguish between patients with or without postoperative infections. No differences were found in the number of leucocytes, time in hospital and other paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Four studies involving 933 pregnant women compared the effect of penicillins combine with enzyme inhibitors with penicillins alone. [9,10,20,23] The penicillins used in these studies are ampicillin (/sulbactam), piperacillin (/tazobactam) and amoxycillin (/clavulanic acid). The outcomes reported in these studies are endometritis, fever, urinary tract infection, and wound infection in mothers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies involving 933 pregnant women compared the effect of penicillins combine with enzyme inhibitors with penicillins alone. [9,10,20,23] The penicillins used in these studies are ampicillin (/sulbactam), piperacillin (/tazobactam) and amoxycillin (/clavulanic acid). The outcomes reported in these studies are endometritis, fever, urinary tract infection, and wound infection in mothers.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Results from the meta-analysis of 2 studies that reported wound infection showed there was no difference in rates of wound infection (RR 0.78, 95% CI 0.19–3.12, I 2 23%; participants = 640). [10,20] One small study found no evidence of a difference in the number of women requiring length of hospital stay > 4 days (RR 0.91, 95% CI 0.50–1.67; participants = 91). [9] Two trials reported no adverse events in any treatment arm, and so the risk ratio was not possible to calculate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation